Provision of Clean Water at Bukit Kunci Tourist Site Using Electricity from Solar Power Plant: Penyediaan Air Bersih di Tempat Wisata Bukit Kunci Menggunakan Listrik dari Pembangkit Listrik Tenaga Surya - Eva Hertnacahyani Herraprastanti; Hendri Suryanto; Suluh Jatmiko; Teguh Yuwono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Bukit Kunci in Bangowan Village, Jiken District, Blora, is a tourist destination offering flower gardens, photo spots, camping areas, and glamping houses. However, the location faces water supply issues, particularly for the bathroom and prayer room needs. Currently, water is pumped from a traditional well using a small centrifugal pump, but limitations in pump capacity and electricity make it difficult for water to reach the surface with a large flow rate. The PKM program aims to meet the clean water needs in Bukit Kunci, provide additional electricity from a solar power plant, and enhance the partner's knowledge in operating and maintaining solar power plant equipment. Test results showed that the water pump powered by a solar power plant was able to function well, with a flow rate of 10 liters per minute and a time of 2.9 hours to fill a 1200-liter tank. Additionally, a 200 Watt Peak solar power plant was used to operate a 770 Watt water pump with a 1000 Watt inverter and a 1000 Ah battery.Through training, the partner's knowledge of solar power plant operation and installation improved. The community’s income increased by 50% after their water needs were met. In the future, increasing the capacity of the solar power plant is expected to make Bangowan Village an Energy Independent Village, without reliance on the national electricity grid (PLN)